ASSESSMENT OF INFORMATION SECURITY RISKS USE FUZZY INFERENCE MODEL (FIS) - Lutfi Nukman; Rahmat Kurniawan; Achmad Solichin (Informatika, Universitas Jenderal Soedirman, 2023)
Risk analysis is the process of systematically using information to identify and assess risks. This process how to analyze potential information security failure scenarios and the consequences of loss of confidentiality, integrity and preservation Availability of stored information values. Risk assessment is the process of comparing estimated risks against predetermined risk evaluation criteria to determine the level and priority of risk. This operation is performed using the retrieved data Risk analysis results for informed decision making future risk management measures; It is said that this cyber attack could lead to cyber warfare and cyber interference that disrupt national security and sovereignty. All of the above cyber threats are said to have the potential to threaten national assets. Institutions/companies around the world, especially those stored in his ISMS.